Vulnerability Study of Coastal Communities in the East Lombok in Facing the Impact of Climate Change - Ichsan, Andi Chairil; Waru, Tenri (Journal of Sylva Indonesiana, 2019)
This study aims to assess the vulnerability of coastal communities to climate change in eastern lombok district by examining exposure, sensitivity and adaptation capacity in ten coastal villages in East Lombok regency. The basic concept of the implementation of this study was constructed qualitatively, using a participatory approach. The method of study was adopted from the PRA (Participatory Rural Appraisal) method with adjustments to coastal and marine context contexts called Indonesian climath adaptation tools for coastal habitat (I-CATCH). The results of this study indicate that most of the villages that are the focus of the implementation of this study have moderate to high vulnerability levels. The impact of the occurrence of climate disaster sufficient to burden the community both from the physical, social, and economic aspects. Thus, it takes a systematic planning and integrated with existing policies to ensure its implementation in the field